Optimizing Biodegradable Waste Conversion with IoT-Based Bioreactor System - Junus, Mochammad; Mustain, Asalil; Putra, Indra Lukmana (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
In Indonesia, the problem of organic waste continues to grow in parallel with population increase and urbanization. However, the management of organic waste still relies on conventional methods that are often ineffective. Conversely, organic waste holds significant potential to be transformed into organic fertilizer and renewable energy through appropriate technological approaches. This study aims to design and implement an organic waste management system that incorporates automatic sorting and biogas conversion. The system is integrated with an Internet of Things (IoT)-based monitoring system at the 3R Integrated Waste Processing Site (TPST 3R) in Mulyoagung, Malang Regency. The system consists of an anaerobic bioreactor that produces methane gas and liquid fertilizer, an automatic sorting unit equipped with color, IR, and weight sensors, and an IoT dashboard for real-time monitoring of temperature, pH, and gas pressure. The research employed both technical and participatory methods, including community training and processing output evaluation. Results indicate a sorting efficiency of up to 92%, biogas production of approximately 22 m³ per ton of organic waste, and a significant increase in community participation. The system proved to be effective, adaptable, and capable of delivering positive social, economic, and environmental impacts.